Subjectivity Study on Anxiety in Clinical Practice of Nursing Students (Medico Legal Update, 2021)
The purpose of this study is to apply Q methodologies to identify and understand the type of anxiety in clinical practiceof nursing students. The study organized the Q population through in-depth interviews to select 30 Q samples that couldrepresent the Q population by coordination with two professors and researchers familiar with the Q methodology, and29 nursing students were selected as P-samples. The data collection was about three months from from August 31to September 11, 2020 and was analyzed using the PQ Method Program. According to this study, nursing studentsanxiety in clinical practice was divided into four types: Type ‘Anxiety related to lack of knowledge’, Type 2‘Anxiety related to self-satisfaction and expectations’, Type 3 ‘Anxiety related to vague expectations’, Type4 ‘Anxiety related to personal factors’. As a result of this study, it is significant that it provided basic data that couldsuggest customized current interventions by analyzing the subjective perception patterns of nursing students aboutclinical practice anxiety. Therefore, it is considered that it is necessary to strengthen the competency of nursing studentsby applying the intervention plan to the comparative course in the future.